2023
DOI: 10.1002/cbic.202200775
|View full text |Cite
|
Sign up to set email alerts
|

Type II Polyketide Synthases: A Bioinformatics‐Driven Approach

Abstract: Bioinformatics has become an indispensable tool for natural products research in the genomic era. One of the key challenges is to accurately convert sequence data of a biosynthetic gene cluster into chemical information such as the enzymatic function or the biosynthetic product structure. Type II polyketide synthase is the most bioinformatically well‐studied class of non‐modular biosynthetic machinery and represents a model system to showcase bioinformatic applications in natural products research. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 155 publications
(223 reference statements)
0
14
0
Order By: Relevance
“…They are known to catalyze diverse reactions, such as epoxidation, oxidative rearrangement, dehydration, nitrogen–nitrogen bond formation, and sulfonamide formation . It should be noted that some type-II PKS cyclases (aromatases) are cupin domain-containing enzymes, although they are not closely related to StrC (Figure S8). Comparison of the crystal structure of RemF, the polyketide cyclase involved in resistomycin biosynthesis, and the modeled structure of StrC generated by ColabFold identified possible metal-binding residues in StrC (His117, Asp123, and His157) (Figure S9), which are completely conserved in the predicted aromatases for fungal alkyl salicylaldehyde derivative biosynthesis (Figure S10).…”
Section: Results and Discussionmentioning
confidence: 99%
“…They are known to catalyze diverse reactions, such as epoxidation, oxidative rearrangement, dehydration, nitrogen–nitrogen bond formation, and sulfonamide formation . It should be noted that some type-II PKS cyclases (aromatases) are cupin domain-containing enzymes, although they are not closely related to StrC (Figure S8). Comparison of the crystal structure of RemF, the polyketide cyclase involved in resistomycin biosynthesis, and the modeled structure of StrC generated by ColabFold identified possible metal-binding residues in StrC (His117, Asp123, and His157) (Figure S9), which are completely conserved in the predicted aromatases for fungal alkyl salicylaldehyde derivative biosynthesis (Figure S10).…”
Section: Results and Discussionmentioning
confidence: 99%
“…A comprehensive review by Rohr and Hertweck breaks down the classes by their unifying themes [139]. Alternatively, a recent review by Xie and Zhang goes in-detail regarding the bioinformatic classification of both the minimal cassette and tailoring enzymes of each major family of compounds in type II PKSs [140], with recent tools aiding in this method of classification for type II PKS products [141].…”
Section: Figurementioning
confidence: 99%
“…Once the length dictated by the CLF is reached, additional transfer back to the KS is not possible and the full-length, ACP-bound polyketide dissociates from the KS-CLF dimer [146]. Downstream cyclases generate the characteristic aromatic core while other tailoring enzymes add functional groups [140].…”
Section: Canonical Type II Pksmentioning
confidence: 99%
“…The KS α subunit catalyzes Claisen-type C–C bond formation employing starter units and malonyl building blocks, whereas the KS β subunit plays an important role in controlling the chain length of type II polyketides and is thus termed “chain length factor” (CLF) . Several studies have shown that CLF phylogeny more tightly correlates with the number of polyketide building block employed rather than the total carbon number. , During polyketide assembly the full-length reactive nascent poly-β-keto chain is often converted to the defined polycyclic skeleton as a result of a combination of ketoreductases, cyclases, and aromatases . Cyclases/aromatases function in a chaperone-like manner, catalyzing regioselective intramolecular aldol condensations en route to ring formation. , In the absence of cyclases/aromatases, spontaneous intramolecular cyclization of the highly reactive poly-β-keto intermediates can occur, leading to the formation of various shunt products. , …”
mentioning
confidence: 99%
“…2 Several studies have shown that CLF phylogeny more tightly correlates with the number of polyketide building block employed rather than the total carbon number. 1,3 During polyketide assembly the fulllength reactive nascent poly-β-keto chain is often converted to the defined polycyclic skeleton as a result of a combination of ketoreductases, cyclases, and aromatases. 4 Cyclases/aromatases function in a chaperone-like manner, catalyzing regioselective intramolecular aldol condensations en route to ring formation.…”
mentioning
confidence: 99%